Development of the KOSHA Proficiency Testing Scheme on Asbestos Analysis in Korea - Jiwoon Kwon; Konghwa Jang; Eunsong Hwang; Ki-Woong Kim (Elsevier, 2017)
This commentary presents the regulatory backgrounds and development of the national proficiency testing (PT) scheme on asbestos analysis in the Republic of Korea. Since 2009, under the amended Occupational Safety and Health Act, the survey of asbestos in buildings and clearance test of asbestos removal works have been mandated to be carried out by the laboratories designated by the Ministry of Employment and Labor (MOEL) in the Republic of Korea. To assess the performance of asbestos laboratories, a PT scheme on asbestos analysis was launched by the Korea Occupational Safety and Health Agency (KOSHA) on behalf of the MOEL in 2007. Participating laboratories are evaluated once a year for fiber counting and bulk asbestos analysis by phase contrast microscopy and polarized light microscopy, respectively. Currently, the number of laboratory enrollments is > 200, and the percentage of passed laboratories is > 90. The current status and several significant changes in operation, sample preparations, and statistics of assigning the reference values of the KOSHA PT scheme on asbestos analysis are presented. Critical retrospect based on the experiences of operating the KOSHA PT scheme suggests considerations for developing a new national PT scheme for asbestos analysis.